STRATEGI KOMUNIKASI PETUGAS POSYANDU MAKARTI DALAM MENINGKATKAN PARTISIPASI IBU BALITA - Muhammad Yudha Prasojo; Mareta Puri Rahastime (Jurnal Riset Multidisiplin Edukasi, 2025)
This study investigates the communication strategies employed by Posyandu Makarti health workers to increase the participation of mothers with toddlers in Posyandu activities  The research is motivated by the observed low attendance and involvement of mothers, which impacts child growth monitoring and preventive healthcare efforts. Utilizing a qualitative approach with descriptive methods, data were gathered through observation, in-depth interviews with Posyandu staff and mothers, and documentation. The findings reveal that Posyandu Makarti personnel implement various communication strategies, including persuasive interpersonal communication, a familial approach, the use of social media (WhatsApp), and direct information dissemination via local community figures . These strategies have proven effective in fostering closer community relationships, raising maternal awareness of the importance of Posyandu services, and encouraging consistent attendance. Challenges identified include limited human resources, some mothers' lack of understanding regarding Posyandu benefits, and economic and time constraints . The study concludes that appropriate and consistent communication strategies play a vital role in increasing the participation of mothers with toddlers in Posyandu programs.